A family of planar differential systems with hyperbolic algebraic limit cycles - Maroua Ghelmi; Aziza Berbache (Electronic Journal of Qualitative Theory of Differential Equations, 2025)
In this paper, we characterize a family of planar polynomial differential systems of degree greater or equal than $n+1$, by presenting polynomial curves of degree $n,$ which generally contain closed components. These systems admit precisely the bounded components of the curve as hyperbolic limit cycles.